2003
DOI: 10.1093/jxb/erg176
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of fatty acid synthase genes, Acl, Fat and Kas, in Capsicum fruit

Abstract: The biosynthesis of capsaicinoids in the placenta of chilli fruit is modelled to require components of the fatty acid synthase (FAS) complex. Three candidate genes for subunits in this complex, Kas, Acl, and Fat, isolated based on differential expression, were characterized. Transcription of these three genes was placental-specific and RNA abundance was positively correlated with degree of pungency. Kas and Acl were mapped to linkage group 1 and Fat to linkage group 6. None of the genes is linked to the pungen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
77
0
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(87 citation statements)
references
References 45 publications
6
77
0
4
Order By: Relevance
“…In comparison, the pungent cultivar 'Demon Red' exhibited abundant levels of Pun1 mRNA. This is consistent with the hypothesis that the level of transcripts accumulating for capsaicinoid-associated genes positively correlates with the level of pungent compounds (Aluru et al, 2003;Curry et al, 1999). The loss of transcription in 'Wonder Bell' (pun1 1 ) has been attributed to a 2.5-kb deletion in the putative promoter region and exon 1.…”
supporting
confidence: 88%
“…In comparison, the pungent cultivar 'Demon Red' exhibited abundant levels of Pun1 mRNA. This is consistent with the hypothesis that the level of transcripts accumulating for capsaicinoid-associated genes positively correlates with the level of pungent compounds (Aluru et al, 2003;Curry et al, 1999). The loss of transcription in 'Wonder Bell' (pun1 1 ) has been attributed to a 2.5-kb deletion in the putative promoter region and exon 1.…”
supporting
confidence: 88%
“…been shown to be highly expressed at 20 DPA and enriched in the placental dissepiment, coinciding with capsaicinoid accumulation (Aluru et al, 2003;Stewart et al, 2005). Recovery of transcripts predicted by our model from this tissue would be consistent with functions related to capsaicinoid biosynthesis.…”
Section: Candidate Gene Sequencessupporting
confidence: 70%
“…While progress has been made in the identification and analysis of genes and proteins found in the historical conceptualization of capsaicinoid biosynthesis (Curry et al, 1999;Kim et al, 2001;Aluru et al, 2003;Lee et al, 2006), the overall capsaicinoid metabolic scheme has not been updated in light of revisions of related pathways in other organisms or considered in terms of its cellular context (Fig. 2).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on the biosynthetic pathway of capsaicinoids in pungent pepper indicated that phenylalanine and valine (or leucine) act as precursors in the synthesis of vanillylamine and acyl moieties, respectively, and that in the last step, capsaicinoids are formed by condensation of vanillylamine and C 7 to C 13 acyl moieties ( Fig. 1) (Fujiwake et al 1980, 1982, Suzuki et al 1981, Curry et al 1999, Aluru et al 2003, Blum et al 2003. More than 10 analogues of naturally occurring capsaicinoids have been recognized in pungent pepper fruits, of which capsaicin (N-(4-hydroxy-3-methoxybenzyl)-8-methyl-trans-6-nonenamide) is the most pungent compound.…”
Section: Introductionmentioning
confidence: 99%